Key Technologies and Applications of Secure Multiparty Computation - Xiaoqiang Guo; Shuai Zhang; Ying Li (Institute of Advanced Engineering and Science, 2013)
With the advent of the information age, the network security is particularly important. The secure multiparty computation is a very important branch of cryptography. It is a hotspot in the field of information security. It expanded the scope of the traditional distributed computing and information security, provided a new computing model for the network collaborative computing. First we introduced several key technologies of secure multiparty computation: secret sharing and verifiable secret sharing, homomorphic public key cryptosystem, mix network, zero knowledge proof, oblivious transfer, millionaire protocol. Second we discussed the applications of secure multiparty computation in electronic voting, electronic auctions, threshold signature, database queries, data mining, mechanical engineering and other fields. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2827